Mesostructure-controlled synthesis of chiral norbornane-bridged periodic mesoporous organosilicas - Hao, Ting Ting; Shi, Jiao Yi; Zhuang, Ting Yan; Wang, Wei David; Li, Fu Chong; Wang, Wei (RSC advances, 2012)
In this contribution, chiral periodic mesoporous organosilica (PMO) materials with three-dimensional body-centered (Im3m) and face-centered (Fm3m) cubic mesostructures were synthesized for the first time. Under acidic conditions and with triblock copolymer F127 as the template, an Im3m-type chiral PMO was obtained with spherical morphology from the self-condensation of chiral norbornane-bridged precursor 1. In contrast, using triblock copolymer P123 as the template and with the aid of a co-surfactant, Gemini surfactant C₁₄₋₆₋₁₄, an Fm3m-type chiral PMO was obtained with an unprecedented pumpkin-like morphology from the self-condensation of chiral precursor 1. The synthetic conditions such as the stirring, standing, and aging time are crucial for the mesostructure and morphology of the synthesized chiral PMO materials.